PENGARUH KEBIJAKAN ANGGARAN TERHADAP KINERJA PENGELOLA KEUANGAN KABUPATEN KARAWANG - Evi Selvi (Value : Journal of Management and Business, 2017)
This research aim to analyze the influence of execution of policy of budget base on performance to interest of organizer of area in improving effectiveness of use of budget of acceptance and expense of area of regency Karawang.Researcher specify three variable namely execution of policy of budget base on performance (X), competition of area budget organizer (Y), improvement to effectiveness of use of budget of acceptance and area expense (Z). Method used in this research to descriptive survey analyze, later then level of sample 76 responder (slovin) amount of responder 336 responder, using technique of cluster random sampling and data technique collecting through observation, enquette, and study documentation, and also process examination of special hypothesis use band path analysis.Result of examination of especial hypothesis show that execution of budget policy base on performance given influenced manifestly and positive to interest of organizer of budget of area in improvement of effectiveness to use of budget of acceptance and area expense the amount is 49.3%, the other dissimilar factors of outside research as factors of outside research as factor epsilon give to influence which to be big 50.7% enough influence to finance region management, some finding which is becoming problems from research result that is budget policy execution base on performance have not optimal yet, it is still not yet to walk well the area finance organizer interest and still lower area expense and acceptance budget use effectiveness improvement.Writer suggest that in service to gift to improve budget discipline which relate to guidance or order which base on it, that is laws, governmental regulation, ministrial descree, by law of regional leader decision, and also comprehend to two deepening policy hit stages to steps and finance management in decision making.Keywords : Policy, Performance, Budget